PENGARUH PENILAIAN BERBASIS KELAS TERHADAP HASIL BELAJAR SISWA DI KELAS X.1 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SMA NEGERI 1 KUANTAN MUDIK - Marlina Marlina; Bustanur Bustanur; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
According to the title, this research was held at SMA Negeri 1 Kuantan mudik. To facilitate the research, the problem was formulated, namely, the role of the teacher in the assessment, the factors that influence the assessment and the effect of class-based assessment on student learning outcomes in PAI subjects in SMA Negeri 1 Kuantan mudik. " on student learning outcomes in Islamic Education subjects in class X.1 SMA Negeri 1 Kuantan Mudik.The population in this study were 1 teacher of Islamic Religious Education subject and 36 students consisting of 26 girls and 10 boys. Data collection techniques used observation, interviews and documentation. While the data analysis technique is done by after the data is obtained, then it is classified into two groups, namely qualitative data and quantitative data. The qualitative data is described in words or sentences. And to know the influence as evidenced by the produc moment formula which results 0.000124.From the results of the produc moment formula above, the result is r xy = 0.000124 which determines the influence of student learning outcomes. From these results, it can be seen that there is an effect of class-based assessment on student learning outcomes.